2014
DOI: 10.1590/s1516-8913201402176
|View full text |Cite
|
Sign up to set email alerts
|

Electronic tongue system to evaluate flavor of soybean (Glycine Max (L.) Merrill) genotypes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…E-tongues turn electrical signals into relish signals to reflect the taste information of food. They have a small threshold of sensation, and the subjectivity of sensory evaluation can be excluded [ 41 ]. As shown in Figure 8 A, the cumulative contribution rates of PC1 (74.9%) and PC2 (19.6%) were 94.5%, indicating that most taste information was reflected.…”
Section: Resultsmentioning
confidence: 99%
“…E-tongues turn electrical signals into relish signals to reflect the taste information of food. They have a small threshold of sensation, and the subjectivity of sensory evaluation can be excluded [ 41 ]. As shown in Figure 8 A, the cumulative contribution rates of PC1 (74.9%) and PC2 (19.6%) were 94.5%, indicating that most taste information was reflected.…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid content is an important factor, which mainly affects the eating quality aspect of umami of vegetable soybean (Silva et al, 2012;Zoldan et al, 2014). Masuda (1991) showed that the content of starch, sucrose, fructose, glutamic acid and alanine in vegetable soybean was higher, therefore, the flavor was enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic tongues transform electrical signals into savor signals to convey taste information of food. Due to their low threshold for sensation, subjectivity in sensory assessments can be ignored (Zoldan et al, 2014). As shown in Figure 1b, the cumulative contribution rates of the first principal component (PC1) (47.83%) and the second principal component (PC2) (23.82%) were 71.65%.…”
Section: Electronic Tonguementioning
confidence: 99%